Pengaruh Intellectual Capital (IC), Good Corporate Governance (GCG), Dan Islamic Corporate Social Responsibility (ICSR) Terhadap Nilai Perusahan Dengan Profitabilitas Sebagai Variabel Intervening - Muhammad Erfani; Yusvita Nena (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2022)
The results of this study show that Intellectual Capital (IC) has a negative effect on Firm Value, and Good Corporate Governance (GCG) has no effect on Firm Value. Islamic Corporate Social Responsibility (ICSR) does not affect firm value. Profitability has a positive effect on firm value. Intellectual Capital (IC) does not affect Profitability. Good Corporate Governance (GCG) hurts profitability. Islamic Corporate Social Responsibility (ICSR) does not affect profitability. Profitability does not mediate the relationship between Intellectual Capital (IC) and Firm Value. Profitability does not mediate the relationship between Good Corporate Governance (GCG) and Firm Value. Profitability does not mediate the relationship between Islamic Corporate Social Responsibility (ICSR) and Firm Value